Mini Factory Inkubator Portabel Untuk Bayi Prematur di Aceh - Ratna Sary; Irwansyah Irwansyah; Sarwo Edhy S; zulfan zulfan; Dedi Afandi; Asbar Asbar; Dandi Bachtiar (Universitas Teuku Umar, 2022)
Indonesia's infant mortality rate is still relatively high when compared to other countries in Southeast Asia. This is caused by many things, including inadequate health facilities for underprivileged communities in rural areas. One solution that can be done is to make incubator equipment that is simple but reliable enough so that it can be loaned out for free to underprivileged families in need. Mini Factory for Portable Incubator is a fabrication activity carried out at the USK Mechanical Engineering Department that aims to produce incubator units designed by experts from the University of Indonesia. This fabrication activity is the result of a collaboration with BFLF Indonesia which funds program activities. The resulting incubator is then handed over to the BFLF Indonesia institution to then distribute it to underprivileged families in need on a free loan basis. The main target is underprivileged families in the province of Aceh. Another outcome is the wide publication of the Acehnese people through the mass media, both print and online.